[Laiškas] / Hope Džeimsas (James) - Tadui Vrublevskiui. - (:unkn) unknown (My University, 1925)
1 laiškas apie neįvykusį susitikimą ir reikalų aptarimą.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Vrublevskis, Tadas Stanislovas, 1858-1925; Hope, Džeimsas (James)